Differentiated Learning-Based Interactive Multimedia: An Effort to Improve Learning Outcomes on the Topic of Ecosystems for Grade V Elementary School Students - Astri Muliawati; Erwin Putera Permana; Nurita Primasatya (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2026)
The implementation of the Merdeka Curriculum requires learning processes that accommodate students’ diverse learning needs. This study aimed to develop differentiated learning-based interactive multimedia on ecosystem material and to examine its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were 28 fifth-grade students of SDN Lirboyo 2 Kediri City, involved in both limited-scale and large-scale trials. Data were collected through observations, interviews, questionnaires, validation sheets, and pretest-posttest assessments, and were analyzed using descriptive quantitative techniques with percentage scores and N-Gain analysis. The results indicated that the developed multimedia achieved a validity score of 96% (very valid), a practicality score of 90% (very practical), and an N-Gain score of 0.84 (high). Therefore, the differentiated learning-based interactive multimedia was considered valid, practical, and effective in improving students’ learning outcomes on ecosystem material.